STRATEGI PENGEMBANGAN BISNIS UKM GUNA MENINGKATKAN PENDAPATAN KARYAWAN PADA USAHA TOKO ROTI FUTRY MAROS DI MAROS SULAWESI SELATAN - Fitriany Fitriany (Jurnal Bisnis dan Kewirausahaan, 2019)
The development of Small and Medium Enterprises (SMEs) is a very important thing, because SMEs have a very important role in the economic growth of a country, and SMEs are able to withstand various economic crises that have occurred. This research was conducted at the Futry Bakery in Maros, South Sulawesi, aimed at finding out business development strategies and increasing employee income. The data analysis method used is a qualitative method. The results showed that the development strategy carried out by UKM Roti futry in Maros South Sulawesi used a marketing mix which included halal products, affordable prices, and transparent promotions. The strategy is carried out by the company by generating an increase in sales turnover. However, the company has not been able to provide wages in accordance with the stipulated by the government through the stipulation of the UMR because the wage system applied by the company still uses a wage system based on employee performance.